Formulation and Evaluation of Biodegradable Sustained Release Aceprophyline Cow Urine Nanoparticle for the Treatment of Asthma - P.Sumathy; Ranganathan Babujanarthanam (International Journal of Pharmacy and Analytical Research, 2015)
The objective of present investigation was to evaluate the entrapment efficiency of the anti-asthma drug Aceprophyline, using natural polymer of different ratio (1:1 to 1:3) and study the effect of this entrapment on the drug release properties. The present study relates to such precious and holy animal derived material cow urine used as a medium and improves the anti-asthmatic activities. The morphology of the nano particles was evaluated using a scanning electron microscope, which showed a round and spherical shape with smooth surface. The result of ratio (1:3) showed a good encapsulation efficiency of 98.29%.Aceprophyline nanoparticles was confirmed by FTIR, DSC and quantitated by UV prepared nanoparticles appeared spherical with round drug core in transmission electron microscopy studies. The release date of Aceprophyline from sodium alginate cow urine nanoparticles was much lower than that HPMC K100 cow urine nanoparticle. Evaluation of release data reveals that release of Aceprophyline with cow urine nanoparticles followed the zero orders, whereas sodium alginate cow urine nanoparticles shows as sustained dispersive drug release was observed invitro one releasing the drug pay load over a period of 16hr. embedding Aceprophyline nanoparticles in alginate provided sustain release. They also offered better pharmacokinetic properties to the drug than afforded by the free drug itself. The cow urine nanoparticle method developed a good choice for one development of sustained anti-asthmatic drug therapy. Improve the patient compliance, reduce the side effects.